2021
DOI: 10.31234/osf.io/xr4su
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparing visual memories to similar visual inputs risks lasting memory distortion

Abstract: Maintaining perceptual experiences in visual working memory (VWM) allows us to flexibly accomplish various tasks, but some tasks come at a price. For example, comparing VWM representations to novel perceptual inputs can induce inadvertent memory distortions. If these distortions persist, they may explain why everyday memories often become unreliable after people perform perceptual comparisons (e.g., eyewitness testimony). Here, we conducted two experiments to assess the consequences of perceptual comparisons u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Although we did not use any secondary task to distract attention away from the original WM representation prior to the onset of the similar probe, it is possible that the similarity-induced memory bias happens only when a WM is compared with a similar input too soon after encoding. We tested this possibility in a follow-up study (Saito et al, 2021) by directly manipulating the interval between memory encoding and similarity judgments. Here, we replicated the similarity-induced memory bias even when participants performed a similarity judgment between a perceptual input and a memory encoded 24 hr before by retrieving it into WM (Atkinson & Shiffrin, 1968; Cowan, 1999; Fukuda & Woodman, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Although we did not use any secondary task to distract attention away from the original WM representation prior to the onset of the similar probe, it is possible that the similarity-induced memory bias happens only when a WM is compared with a similar input too soon after encoding. We tested this possibility in a follow-up study (Saito et al, 2021) by directly manipulating the interval between memory encoding and similarity judgments. Here, we replicated the similarity-induced memory bias even when participants performed a similarity judgment between a perceptual input and a memory encoded 24 hr before by retrieving it into WM (Atkinson & Shiffrin, 1968; Cowan, 1999; Fukuda & Woodman, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In the present experiments, we tested the prediction that using memories in perceptual comparisons can trigger distinct forms of memory updating. Specifically, we predicted that perceived similarity between mnemonic and perceptual representations would result in representational integration, as demonstrated previously (Fukuda et al, 2022;Saito et al, 2021), and that perceived sameness would result in probabilistic replacement by the perceptual representation. We based this prediction on the fact that perceived sameness between sequential stimuli indicates a sense of shared identity that is fundamentally untrue for perceived similarity and allows individuals to rely on the more recent stimulus to facilitate their behavioral goals.…”
Section: Discussionmentioning
confidence: 85%
“…An immediate next step will be to confirm that memory replacement following 'same' judgments reflects a bona fide change in the memory and not a temporary phenomenon brought about by decisional processes at the time of the report. Previous work has shown that biases following 'similar' judgments are recalled again 24-hours later, suggesting that memory errors following perceptual comparisons reflect veridical changes in memory that may be permanent (Saito et al, 2021). As such, it is not unreasonable to predict that memory errors following 'same' judgments reflect an analogous process.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations